Effectiveness of The Larvicide Combination Extract of Basil (Ocimum basilicum) Leaves And Soursop (Annona muricata) Leaves Against Aedes aegypti Larva - Shafrina Rohma, Hanna; Mufidah, Hartalina; Anggia Destiawan, Rian; Trianggaluh Fauziah, Dina (LPPM Universitas dr. Soebandi, 2024)
Background: Dengue hemorrhagic fever (DHF) is an acute febrile illness caused by dengue virus infection which is transmitted through the bite of the Aedes aegypti mosquito. An alternative method that can be used is a vegetable larvicide to eradicate Aedes aegypti larvae. Basil leaf extracts (Ocimum basilicum) and soursop leaves (Annona muricata) contain flavonoids, saponins, alkaloids, tannins and essential oils as larvicide compounds. Purpose: This study aims to determine the effectiveness of the larvicidal combination of basil (Ocimum basilicum) and soursop (Nnona muricata) leaf extracts against Aedes aegypti larvae at concentrations of 5%, 10%, 15% and 20%. Methods: This type of research is descriptive quantitative research with an experimental design. This study used 6 samples of Aedes aegypti larvae at each concentration. The treatment stage was carried out by adding a combination of basil (Ocimum basilicum) and soursop leaf (Annona muricata) leaf extracts in concentrations of 5%, 10%, 15% and 20% into an Erlenmeyer flask containing larvae and distilled water. Calculate the number of deaths at 30 minutes, 1 hour, 2 hours and 3 hours. Results: The results of this study showed larval mortality at a concentration of 5%, namely 0 larvae in 30 minutes, 1 larva in 1 hour, 2 larvae in 2 hours and 3 larvae in 3 hours. Larval mortality at a concentration of 10% is 1 larva in 30 minutes, 2 larvae in 1 hour, 3 larvae in 2 hours and 0 in 3 hours. Larval mortality at a concentration of 15% is 2 larvae in 30 minutes, 3 larvae in 1 hour, 1 larva in 2 hours and 0 larvae in 3 hours. Larval mortality at a concentration of 20% was 3 larvae in 30 minutes, 3 larvae in 1 hour and 0 larvae in 2 and 3 hours. Conclusions: The combination of basil (Ocimum basilicum) and soursop leaf (Annona muricata) leaf extracts is most effective as a larvicide at a concentration of 20% with a death time of 30 minutes.